Efektivitas Metode Pembelajaran Al-Qur'an dalam Meningkatkan Kemampuan Membaca Siswa di Madrasah Ibtidaiyah - Nimim Ali; Jumahir; Mursyidi (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2024)
The importance of effective Qur'anic reading instruction in shaping students' religious understanding and literacy skills. This study aims to analyse the effectiveness of Qur'anic learning methods in improving students' reading skills at Madrasah Ibtidaiyah Negeri 1 Banggai. This study used a quantitative approach with an experimental design to measure the effect of learning methods on improving the ability to read the Qur'an. The research subjects were 4th grade students of Madrasah Ibtidaiyah Negeri 1 Banggai consisting of 30 students, which were divided into two groups, namely the experimental group and the control group. Data collection methods used Al-Qur'an reading tests before and after treatment, as well as observation of the learning process applied. The learning methods used in this study were the iqra' and tahsin methods which focused on improving the technique of reading and pronouncing the hijaiyah letters correctly. The collected data were analysed using paired sample t-test to determine the significant difference between the test scores before and after treatment. The results showed a significant improvement in students' Qur'an reading ability after the implementation of the intended learning method. The average student test score increased from 60 to 85 after the application of the method. Based on these findings, it can be concluded that the Qur'anic learning method used in Madrasah Ibtidaiyah Negeri 1 Banggai is effective in improving students' reading ability